1
$\begingroup$

Let $f(x)=(x^2+6x+9)^{50}-4x+3$, and let $r_1,r_2,\ldots,r_{100}$ be the roots of >$f(x)$.

Compute $(r_1+3)^{100}+(r_2+3)^{100}+\cdots+(r_{100}+3)^{100}$.

How would I compute this? How to factor it?

$\endgroup$
4
$\begingroup$

Note that for any $r$ that is the root of $(x^2+6x+9)^{50}-4x+3$, note that it satisfies $$(r^2+6r+9)^{50}=4r-3 \iff (r+3)^{100}=4r-3$$ So $$\sum_{i=1}^{100} (r_{i}+3)^{100}=\sum_{i=1}^{100} (4r_{i}-3)=4 \times \text{(Sum of roots)}-300$$Expanding $(x+3)^{100}-4x+3$ using the binomial theorem, we get $$f(x)=x^{100}+\color{red}{300}x^{99}+\dots$$ So the sum of roots is equal to $-300$. The answer is $-1500$.

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

Observe that $(x^2+6x+9)=(x+3)^2$, so $f(x)=(x+3)^{100}-4x+3$. Since each root satisfies $f(r_i)=0$, we know that $(r_i+3)^{100}=4r_i-3$. Therefore, you're interested in $$ 4\sum r_i-300. $$ The sum of the roots of a polynomial of degree $n$ is the negative of the coefficient of $x^{n-1}$. In this case, the $x^{99}$ term has coefficient $3\binom{100}{99}$ by the binomial theorem. Therefore, the sum is $$ -1200-300=-1500. $$

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

We begin by observing that $x^2+6x+9 = (x+3)^2$

Denote $f(x) = (x^2+6x+9)^{50} - 4x +3 = (x+3)^{100}-4x+3$

$\{r_i\}_{1\leq i \leq 100}$ are roots of this polynomial so $f(r_i)= (r_i+3)^{100}-4r_i+3 = 0$ $\forall 1 \leq i \leq 100$

By Vieta's formula, the sum of roots is negative of coefficient of $x^{99}$ term in $f(x)$ which by Binomial Expansion turns out to be $-\binom{100}{1}3^1 = -300$

Now, we just need to make some manipulations, as follows:

$$(r_i+3)^{100} - 4r_i + 3 = 0 \implies (r_i+3)^{100} = 4r_i - 3$$

Therefore,

$$\sum_{i=1}^{100} (r_i+3)^{100} = \sum_{i=1}^{100} 4r_i - 3 = 4 \left(\sum_{i=1}^{100} r_i\right) -300 = -1500$$

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

Hint:

The equation is none other than $$\bigl((x+3)^2\bigr)^{50}-4x+3=(x+3)^{100}-4x+3=0.$$ Hence the roots $r_i$ satisfy $$(r_i+3)^{100}=4r_i-3.$$

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Yes, a typo. I initially had expressed everything in function of $u=x+3$,and I had a different constant term. Fixed. Thanks for pointing it! $\endgroup$ – Bernard Feb 28 '17 at 13:52

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.